The Effect Of Market Orientation, Competitive Advantage, And Marketing Capabilities On The Marketing Performance Of Small And Medium-Sized Enterprises In The Crafts Industry Yogyakarta - Rahayu, Suryaningtyas; Nuvriasari , Audita (JURNAL ILMU MANAJEMEN, 2025)
This study aims to analyze the effect of market orientation, competitive advantage, and marketing capabilities on the marketing performance of craft MSMEs in Yogyakarta. Using a quantitative approach, this study involved 100 respondents selected through purposive sampling with the criteria of craft MSMEs that have been operating for at least three years. Data were collected using questionnaires and tested using multiple linear regression analysis. The results show that market orientation has a positive and significant effect on marketing performance, confirming the importance of understanding customer needs and responsiveness to market dynamics. Marketing capabilities also proved to have a positive and significant effect, indicating that the ability to conduct market research, manage customer relationships, and develop marketing strategies contributes directly to improved marketing performance. However, competitive advantage did not show a significant effect, indicating that product differentiation and uniqueness possessed by SMEs have not been able to directly drive improvements in marketing performance. These findings emphasize that strengthening market orientation and marketing capabilities are key factors in improving the competitiveness and performance of craft SMEs in Yogyakarta.